IoT-Based Transmission Tower Monitoring Communications and Visualization Platform - Mohd Alias M.R.N.; Mohd Dzaki D.R.; Din N.M.; Deros S.N.M.; Passarella R.; Amier Chaai A.E.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Damage detection; Electric power system protection; Electric power transmission; Fault detection; Internet of things; Mobile computing; Network layers; Smart power grids; Visualization; Wi-Fi; Communication platforms; Dashboard; Flutter; Grafana; Influxdb; IoT; Mobile applications; Monitoring system; Smart grid; Transmission tower; Wind